Strategy Proposal for the linking and follow-up of graduates of the curricula of the School of Library Science, Documentation and Information of the National University of Costa Rica (2022-2026) - Montero Bustabad, Pedro (2024)
For the present investigation, a compilation and organization of information sources was carried out that dealt with the issue of linking and monitoring the graduates of the different study programs of the career of the School of Library Science, Documentation and Information (EBDI) of the National University of Costa Rica. The selected contents of the sources consulted were analyzed, identifying the current need to create a strategy that would guide and coordinate all the new initiatives to strengthen the link and facilitate the follow-up of these professionals with the EBDI, taking into account the topics of interest identified for updating, and continuous training. This proposal has the objective of strengthening the link, monitoring and communication between both parties considered through a strategy for the period 2022-2026 that would facilitate updated knowledge of labor market conditions, the management of alliances and the interests of updating and education. permanent considering the experience and learning achieved by graduates. This academic exercise was carried out with a mixed approach in which different techniques and sources of qualitative and quantitative information were used, facilitating the obtaining of results such as: a description of the context and identification of the updating needs of the people graduates, the identification of the context and needs of both the graduates and the EBDI in maintaining constant links and communication with each other and a strategy proposal for linking and monitoring these professionals with the EBDI.